Pharmacotherapeutic Applications, Mechanisms, and Clinical Management of Neostigmine: Implications for Pharmacists, Pharmacy Technicians, and - Alrasheedi, Salah Mohammed Mufleh; Khalid Mohammed Albalawi; Abdulrahman Abdullah Suwayyid Almutairy; Fahad Saed Saeed AL Dughaylibi; SaudMarfua Alsulami; Mountadhar Hussain Alzainaldeen; Zainab Radhi ALMAHDUD; Rami Ahmad Almalki; Sayer Ali Naif Alshammari; Meshal Mohammed Alshamrani; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Neostigmine is a reversible acetylcholinesterase inhibitor widely used in clinical practice, primarily for reversing non-depolarizing neuromuscular blockade during anesthesia. Its pharmacologic actions, peripheral selectivity, and broad therapeutic relevance necessitate a clear understanding of its clinical applications, safety profile, and monitoring requirements. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to summarize the pharmacotherapeutic applications, mechanisms, pharmacokinetics, administration considerations, adverse effects, and clinical precautions associated with neostigmine to support informed decision-making among pharmacists and healthcare professionals. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The article synthesizes peer-reviewed evidence and guideline recommendations, emphasizing FDA-approved indications, off-label uses such as acute colonic pseudo-obstruction, pharmacokinetic characteristics, dosing strategies, and monitoring standards. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Neostigmine effectively reverses neuromuscular blockade by increasing acetylcholine availability at the neuromuscular junction. It demonstrates predictable pharmacodynamics, though clearance varies significantly with renal function. Off-label use in acute colonic pseudo-obstruction is supported by gastrointestinal and surgical society guidelines. Adverse effects include bradyarrhythmias, bronchoconstriction, excessive secretions, and paradoxical muscle weakness; these risks necessitate co-administration with antimuscarinic agents and continuous monitoring. Drug interactions, contraindications, and patient-specific considerations (pregnancy, renal impairment, pediatrics, geriatrics) further inform individualized therapy. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Neostigmine remains an essential pharmacologic tool for perioperative care and neuromuscular management. Optimizing its use requires precise dosing, vigilant monitoring, awareness of patient-specific risks, and interprofessional collaboration to enhance outcomes and minimize complications.